A New Approach to the Chronology of Caves 268/272/275 in the Dunhuang Mogao Grottoes: Combining Radiocarbon Dates and Archaeological Information within a Bayesian Statistical Framework. Issue 2 (25th April 2018) - Guo, Qinglin; Staff, Richard A; Lu, Chun; Liu, Cheng; Dee, Michael; Chen, Ying; Pollard, A Mark; Rawson, Jessica; Su, Bomin; Liu, Ruiliang
Abstract: The construction chronology of three of the earliest Dunhuang Mogao Grottoes (Caves 268, 272, and 275) has been the subject of ongoing debate for over half a century. This chronology is a crucial topic in terms of further understanding of the establishment of the Dunhuang Mogao Grottoes, early Buddhism in the Gansu corridor, and its relationship with Buddhism developed in the Central Plains. Building upon archaeological, art historical and radiocarbon ( 14 C) dating studies, we integrate new 14 C data with these previously published findings utilizing Bayesian statistical modeling to improve the chronological resolution of this issue. Thus, we determine that all three of these caves were constructed around AD 410–440, suggesting coeval rather than sequential construction.